Menggagas Isu Keadilan di Masa Depan sebagai Peran Kebijakan untuk Keseimbangan Generasi - Eva Monalisa Vebry Kusuma; Gunawan Santoso; Lestari, Tuti; Solehun; Primantiko, Retno; Pransiska, Liya; Baiq Dina Erika Wardiningtias (Jurnal Pendidikan Transformatif, 2023)
This research aims to explore and initiate policy solutions that can shape a more just and balanced future for various generations in society. The main focus is on the key role of policy in achieving generational balance and creating an environment that supports justice in various aspects of life. Through in-depth analysis of economic, educational, health and environmental issues, this research aims to develop policy recommendations that can bring positive change. The research methods used involve a cross-generational approach survey, interviews with key stakeholders, and analysis of secondary data from previous policies. It is hoped that the results of this research will provide in-depth insight into the challenges and opportunities in achieving generational balance, as well as provide a basis for formulating effective policies. The results of this research show that policies that promote equal access to education, employment opportunities, and health services have a positive impact on generational balance. In addition, it was found that active participation from the community and stakeholders in policy making was the main key to success. Recommendations for future policy include education sector reform, improving access to health services, and innovative strategies to promote work-life balance. This research contributes to the public policy literature by providing a better understanding of the role of policy in shaping a just and equitable future. The practical implications involve implementing policies that are inclusive and sustainable, taking into account intergenerational dynamics and supporting the well-being of all levels of society.